Antioxidant and antimicrobial efficacy of a biflavonoid, amentoflavone from Nandina domestica in vitro and in minced chicken meat and apple juice food models. (15th January 2019) - Bajpai, Vivek K.; Park, InWha; Lee, JungIn; Shukla, Shruti; Nile, Shivraj Hariram; Chun, Hyang Sook; Khan, Imran; Oh, Seo Yeong; Lee, Hoomin; Huh, Yun Suk; Na, MinKyun; Han, Young-Kyu
Highlights: A biflavonoid, amentoflavone was characterized based on the NMR analysis. Amentoflavone demonstrated significant antioxidant potential. Amentoflavone compromised membrane permeability of foodborne pathogens. Studies of SEM and TEM confirmed a mechanistic role of amentoflavone. Amentoflavone displayed microbial food safety in meat and apple juice. Abstract: A biflavonoid, amentoflavone isolated from Nandina domestica and characterized by NMR spectral-data analyses was assessed for its antioxidant, and antibacterial potential in vitro and in food-model systems. Amentoflavone exhibited potent antioxidant ability (19.21–75.52%) on scavenging DPPH, ABTS, superoxide, and hydroxyl radicals. Fluorescent images confirmed bacterial membrane depolarization of both the tested pathogens Staphylococcus aureus and Escherichia coli, with a significant reduction in cell viabilities at their respective MIC of 62.5 and 125 µg/mL. Increasing rates of membrane permeability observed in 260 nm-absorbing material, potassium ion, extracellular ATP, and relative electrical conductivity assays confirmed antibacterial mechanistic role of amentoflavone as also evidenced by microscopic studies of SEM and TEM. There was a marked inhibitory effect of amentoflavone with a significant reduction in cell counts of S. aureus and E. coli in minced chicken and apple juice at 4 °C, thus suggesting its nutritional enhancing efficacy as a natural antioxidant and antimicrobial agent.